Chemo-enzymatic synthesis of the ALG1-CDG biomarker and evaluation of its immunogenicity. Issue 24 (15th December 2020) - Jia, Ji-Xiang; Kalisa, Ndayambaje Yvan; Lu, Tian-Tian; Zhou, Zhifang; Gao, Xiao-Dong; Wang, Ning
Graphical abstract: Abstract: Congenital disorders of glycosylation (CDG) are a growing group diseases that result from defects in genes involved in glycan biosynthesis pathways. One tetrasaccharide, i.e., Neu5Ac-α2, 6-Gal-β1, 4-GlcNAc-β1, 4-GlcNAc, was recently reported as the biomarker of ALG1-CDG, the disease caused by ALG1 deficiency. To develop a novel diagnostic method for ALG1-CDG, chemo-enzymatic synthesis of the tetrasaccharide biomarker linked to phytanyl phosphate and the biomarker's immune stimulation were investigated in this study. The immunization study using liposomes bearing phytanyl-linked tetrasaccharide revealed that they stimulated a moderate immune response. The induced antibody showed strong binding specificity for the ALG1-CDG biomarker, indicating its potential in medical applications.